Technical review on different metal nanoparticles and their formulations on growth, agronomic and economic traits of crop plants - Kumar, Sandeep; Suman, Shivangi; Muthukumar, M.; Mishra, Kuldeep; Bajpai, Anju; Tiwari, Ajay Kumar; Srivastava, Gaurav; Bansal, Shonak; Chaturvedi, Kavita; Maurya, Shubham; Damodaran, T.; Killadi, Bharati; et al. (Frontiers in Nanotechnology, 2025)
Metal nanoparticles (MNPs) are emerging as powerful inputs for sustainable agriculture due to their high surface reactivity, bioavailability, and controlled release properties leading to better resource availability and higher productivity. This technical review critically examines the application of eight metal nanoparticle (MNP) formulations—zinc, iron, copper, silver, calcium, titanium, gold, and selenium—in enhancing agronomic and economic traits in agriculture. The review highlights the potential of these MNPs to improve crop yield, disease resistance, nutrient uptake, and overall plant health, offering insights into their mechanisms of action and practical applications in sustainable farming. ZnO-NPs, Fe2O3-NPs, Cu-NPs, and Ag-NPs have proven to enhance nutrient use efficiency in crops. ZnO and Fe2O3-NPs improve nutrient uptake, boost photosynthesis, and increase stress tolerance, especially to drought and salinity. Cu-NPs and Ag-NPs stand out for their antibacterial and antifungal properties, offering a novel approach to managing plant diseases. Calcium and titanium nanoparticles boost resilience under salt and oxidative stress. Au-NPs and Se-NPs enhance antioxidant activity and growth, but their effects are dose-dependent. Higher MNP concentrations may cause adverse effects, highlighting the need for careful optimization. In conclusion, while metal nanoparticles (MNPs) hold great potential for enhancing crop plant traits, issues such as dosage optimization, formulation protocols, and environmental and toxicological concerns need careful consideration. To overcome these challenges, the integration of green technologies using microbial and phyto-metabolites could provide safer, more sustainable alternatives, ensuring effective and environmentally friendly use of MNPs in agriculture.